Mycorrhizal association of common European tree species shapes biomass and metabolic activity of bacterial and fungal communities in soil. (October 2020) - Heděnec, Petr; Nilsson, Lars Ola; Zheng, Haifeng; Gundersen, Per; Schmidt, Inger Kappel; Rousk, Johannes; Vesterdal, Lars
Abstract: Recent studies have revealed effects of various tree species on soil physical and chemical properties. However, effects of various tree species on composition and activity of soil microbiota and the relevant controls remain poorly understood. We evaluated the influence of tree species associated with two different mycorrhizal types, ectomycorrhiza (EcM) and arbuscular mycorrhiza (AM), on growth, biomass and metabolic activity of soil fungal and bacterial communities using common garden tree species experiments throughout Denmark. The soil microbial communities differed between six European tree species as well as between EcM (beech, lime, oak and spruce) and AM (ash and maple) tree species. The EcM tree species had higher fungal biomass, fungal growth and bacterial biomass, while AM species showed higher bacterial growth. The results indicated that microbial community composition and functioning differed between groups of tree species with distinct litter qualities that generate soil C/N ratio and soil pH differences. The mycorrhizal association only partly explained litter quality and soil microbial species differences since lime was more similar to AM tree species. In addition, our results indicated that tree species-mediated soil pH and C/N ratio were the most important variables shaping microbial communities with a positive effect on bacterial and a negative effect on fungal growth rates. The results suggest that tree species-mediated microbial community composition and activity may be important drivers of the different vertical soil C distribution previously observed in AM and EcM tree species. Highlights: The soil microbial communities differed between six European tree species. The EcM tree species had higher fungal growth and biomass. The AM species showed higher bacterial growth. Tree species effects were driven by litter quality and changed soil properties.